2008
DOI: 10.1007/s10657-007-9042-6
|View full text |Cite
|
Sign up to set email alerts
|

Market structures, political surroundings, and merger remedies: an empirical investigation of the EC’s decisions

Abstract: Merger remedies, Antitrust, European Commission, Discrete choice models, Self-organizing maps, K21, L40, D78,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
10
1
1
Order By: Relevance
“…Explanatory variables invariably fall into two broad categories 5 : S, market shares and concentration, and X, other market characteristics, such as entry barriers, buyer power, excess capacity. The current paper attempts to develop this literature in at least three re-4 Other similar studies include: Davies et al (1999) for abuse of dominance in the UK; Carree et al (2008) for European antitrust cases; Grout and Sondregger (2005) for cartels; Lindsay et al (2003) and Bougette and Turolla (2008) for EC mergers.…”
Section: Previous Literaturementioning
confidence: 99%
“…Explanatory variables invariably fall into two broad categories 5 : S, market shares and concentration, and X, other market characteristics, such as entry barriers, buyer power, excess capacity. The current paper attempts to develop this literature in at least three re-4 Other similar studies include: Davies et al (1999) for abuse of dominance in the UK; Carree et al (2008) for European antitrust cases; Grout and Sondregger (2005) for cartels; Lindsay et al (2003) and Bougette and Turolla (2008) for EC mergers.…”
Section: Previous Literaturementioning
confidence: 99%
“…Explanatory variables invariably fall into two broad categories 5 : S, market shares and concentration, and X, other market characteristics, such as entry barriers, buyer power, excess capacity. The current paper attempts to develop this literature in at least three re-4 Other similar studies include: Davies et al (1999) for abuse of dominance in the UK; Carree et al (2008) for European antitrust cases; Grout and Sondregger (2005) for cartels; Lindsay et al (2003) and Bougette and Turolla (2008) for EC mergers.…”
Section: Previous Literaturementioning
confidence: 99%
“…The remedial action chosen by the Federal Trade Commission in the US follows a relatively similar pattern. The empirical literature, as summarized in Table 1 by Bougette and Turolla (2008), has also shown that structural remedies constitute the most frequent type of remedies. This paper investigates structural remedies, with a focus on divestitures of one special form of assets: the divestiture of differentiated brands to an existing competitor.…”
Section: Introductionmentioning
confidence: 99%